2(k+5)-3=k+18

Simple and best practice solution for 2(k+5)-3=k+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(k+5)-3=k+18 equation:


Simplifying
2(k + 5) + -3 = k + 18

Reorder the terms:
2(5 + k) + -3 = k + 18
(5 * 2 + k * 2) + -3 = k + 18
(10 + 2k) + -3 = k + 18

Reorder the terms:
10 + -3 + 2k = k + 18

Combine like terms: 10 + -3 = 7
7 + 2k = k + 18

Reorder the terms:
7 + 2k = 18 + k

Solving
7 + 2k = 18 + k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1k' to each side of the equation.
7 + 2k + -1k = 18 + k + -1k

Combine like terms: 2k + -1k = 1k
7 + 1k = 18 + k + -1k

Combine like terms: k + -1k = 0
7 + 1k = 18 + 0
7 + 1k = 18

Add '-7' to each side of the equation.
7 + -7 + 1k = 18 + -7

Combine like terms: 7 + -7 = 0
0 + 1k = 18 + -7
1k = 18 + -7

Combine like terms: 18 + -7 = 11
1k = 11

Divide each side by '1'.
k = 11

Simplifying
k = 11

See similar equations:

| Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 | | .5x+.45(30)=49.5 | | -8m+15+9m=-2 | | Y=-4(4)-3 | | x-9+5x-3=5x | | 11x=10x+17 | | Y=-4(-2)-3 | | x-14.6=20 | | 5(k+2)=3(-4) | | -8m+15+9m-2= | | Y=-10(5)-3 | | n+221=333 | | 5m-13=33 | | 9x^4=3x^2-25 | | 5(5x)+12= | | 5(5x+12)= | | 4n+24=2n+42 | | 3p+5=2p+14 | | 2(13.5)+-1.5y+3y=27 |

Equations solver categories